If y=2 cos(logx)+3 sin(logx), prove that `x^2(d^2y)/(dx2)+x dy/dx+y=0`

Advertisement Remove all ads

#### Solution

y=2 cos(logx)+3 sin(logx)

Differentiating both sides with respect to *x*, we get

`dy/dx=2xxd/dx cos(logx)+3xx d/dxsin(log x)`

`=-2sin(logx)xx1/x+3 cos(logx)xx1/x`

`=>x dy/dx=-2 sin(logx)+3 cos(logx)`

Again, differentiating both sides with respect to *x*, we get

`x (d^2y)/(dx^2)+dy/dx=-2cos(logx)xx1/x-3 sin(logx)xx1/x`

`x^2 (d^2y)/(dx^2)+xdy/dx=-[2 cos(logx)+3sin(logx)]`

`x^2 (d^2y)/(dx^2)+xdy/dx=-y`

`x^2 (d^2y)/(dx^2)+xdy/dx+y=0`

Concept: Second Order Derivative

Is there an error in this question or solution?

#### APPEARS IN

Advertisement Remove all ads